Measurement of the F2 structure function in deep inelastic e+p scattering using 1994 data from the ZEUS detector at HERA - Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Okrasinski, JR; Repond, J; Stanek, R; Talaga, R; Zhang, H; Mattingly, M; Anselmo, F; et al. (1996)
We present measurements of the structure function F2 in e+p scattering at HERA in the range 3.5 GeV2 < Q2 < 5000 GeV2. A new reconstruction method has allowed a significant improvement in the resolution of the kinematic variables and an extension of the kinematic region covered by the experiment. At Q2 < 35 GeV2 the range in x now spans 6.3 · 10-5 < x < 0.08 providing overlap with measurements from fixed target experiments. At values of Q2 above 1000 GeV2 the x range extends to 0.5. Systematic errors below 5% have been achieved for most of the kinematic region. The structure function rises as x decreases; the rise becomes more pronounced as Q2 increases. The behaviour of the structure function data is well described by next-to-leading order perturbative QCD as implemented in the DGLAP evolution equations. © Springer-Verlag 1996.